Histone Methylation and Transcriptional Regulation in Cardiovascular Disease - Xu, Yong; Fang, Fei (Cardiovascular & Haematological Disorders - Drug Targets, 2014)
Cardiovascular disease (CVD) represents a major health risk to the global population. In disease settings, cells that constitute the vasculature undergo profound changes both morphologically and functionally paralleling alterations in gene expression profile. At the transcriptional level, gene expression is steered by the epigenetic machinery including DNA methyltransferases, histone variants, non-coding regulatory RNAs, chromatin remodeling complexes, and histone modifying enzymes. The N-terminal tails of histones, primarily histones H3 and H4, are post-translationally modified creating a unique platform for transcriptional regulation. This review summarizes our current understanding of the role of histone methylation in modulating the vascular transcriptome and its relevance in CVD with an outlook on future directions.
Keywords: transcriptional regulation